2015
DOI: 10.1111/joor.12314
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Dutch version of the Orofacial Esthetic Scale (OESNL) in dental patients with and without self‐reported tooth wear

Abstract: The aim of this study was to test the psychometric properties of the Dutch version of the Orofacial Esthetic Scale (OES) in dental patients with and without self-reported tooth wear. The English version of the OES was translated into Dutch, following established guidelines for cross-cultural adaptation of health-related quality of life measures. The reliability of the resulting OES-NL was tested in a test-retest study on 343 subjects; its validity was tested with the use of convergent validity on 582 subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…Questionnaires about oral parafunctions , reflux disease , eating disorders and a dry mouth can provide insight into the possible aetiological factors of the worn dentition. Questionnaires can also be helpful for the assessment of the complaints of patients due to their tooth wear, for example impaired oro‐facial aesthetics or limitation in jaw function capability .…”
Section: Diagnostic Modulesmentioning
confidence: 99%
“…Questionnaires about oral parafunctions , reflux disease , eating disorders and a dry mouth can provide insight into the possible aetiological factors of the worn dentition. Questionnaires can also be helpful for the assessment of the complaints of patients due to their tooth wear, for example impaired oro‐facial aesthetics or limitation in jaw function capability .…”
Section: Diagnostic Modulesmentioning
confidence: 99%
“…However, this should not be a limitation. Other studies already proved convergent validity with external ratings of Oro‐facial Appearance, known‐groups validity, responsiveness and test‐retest reliability of the OES . We see no reason why this should be related to the method of administration.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the Oro‐facial Esthetic Scale (OES), an 8‐item instrument, was developed to overcome this drawback and to comprehensively assess Oro‐facial Appearance from the patient perspective . The OES is unidimensional, exhibited good psychometric properties and is available in several languages . Furthermore, norm values were provided for the general population …”
Section: Introductionmentioning
confidence: 99%
“…The OES instead evaluates the overall satisfaction of the patient with his/her esthetic appearance. As the most common instrument used in research, the OES has good psychometric properties and has been adapted cross-culturally to several languages such as; Croatia,Chinese,Albanian,Dutch,Germany,Arabic,and Spanish [25,29,[32][33][34]37,40,41]. Although the instrument developed by Tortopidis et al showed good reliability, there has been no report of its use in other published studies.…”
Section: Discussionmentioning
confidence: 99%